Nyorog Tradition Value in Betawi Societies - Bahagia Bahagia; Rimun Wibowo; Fachruddin Majeri Mangunjaya; Eka Paradila; Nur Afiyah Sulistiyanti; Muhammad Aqil Ibatulloh; Mahesa Rana Kharisma; Muhammad Asyrul Addha; Siti Syafatul Rahmah (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to identify the Islamic religious values contained in the Betawi tradition, namely the Nyorog tradition. The nyorog tradition is a tradition that delivers food between family and neighbors which is usually carried out by Betawi residents at the time of Eid al-Fitr. This research uses qualitative research. The research approach used is Ethnographic Field research. The sample collection technique in this study used the purposive sampling technique. The results of the study show that Nyorog is a tradition in Betawi society that still survives despite experiencing many forms of change. Another finding is that there are social values in the nyorog tradition including the value of friendship between friends because it is a place to build social relationships. Family relationships are also built socially between young people and older people. In addition, nyoroh also contains the value of social assistance because nyorog makes the community close so that if there is a disaster in the family, the family and neighbors will help. There is even a value of social approach to nyorog where when there is a new bride, both parties visit each family from the female and male sides. Nyorog also contains religious values, especially Islam because the behavior in Nyorog activities is in accordance with Islamic teachings.